2004
DOI: 10.1002/pssc.200304415
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and magnetoresistance effect in Co/Au, Ag nano‐structure films produced by pulse electrodeposition

Abstract: We have investigated the relationship between the magnetism and the magnetoresistance effect in the Co/Au, Ag multilayer films with layers produced in the atomic level by pulse electrodeposition method. The magnetoresistance effect is dependent on both the thickness of Co ferromagnetic layer and Ag,Au non-magnetic layers. The magnetization of these films shows the minimum value against the Ag and Au layer thickness. The Ag and Au layer thickness showing the maximum of MR ratio is not of necessary in agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
2
10
0
Order By: Relevance
“…It is clear that these multilayers have a well-defined periodicity, D ¼ 31 Å , calculated by using the Bragg-law. This layer thickness is in agreement with our mass measurement data obtained from the highly sensitive microbalance and energy dispersive X-ray analysis (EDAX) [4]. Fig.…”
supporting
confidence: 85%
“…It is clear that these multilayers have a well-defined periodicity, D ¼ 31 Å , calculated by using the Bragg-law. This layer thickness is in agreement with our mass measurement data obtained from the highly sensitive microbalance and energy dispersive X-ray analysis (EDAX) [4]. Fig.…”
supporting
confidence: 85%
“…The increase in the MR ratio near 30 at % Co seems to be due to the optimum size and distribution of Co grains and inter-granular separation [44], [37]. The low MR values below 30 at% Co can be ascribed to a relatively low concentration of ferromagnetic components leading to fewer magnetic and non-magnetic interfacial scattering sites.…”
Section: B Composition Dependence Of Magnetoresistance Ratiomentioning
confidence: 94%
“…Guo et al [35] reported room temperature MR of 0.5 % for the as-deposited Co-Au alloys and of up to 1.5 % when annealed at 573 K. They found that the grain size of Co increased with the increase of annealing temperature. Previous studies [37], [38] have shown GMR values of up to 4 % for the as-deposited Co/Au multilayers prepared using pulsed-current electrodeposition in the cyanide solution and demonstrated how closely GMR and magnetic properties are correlated with the layer thickness and composition in the as-deposited Co/Ag and Co/Cu nanostructures [38], [39]. However, it is not yet fully clear to what extent deposition current density, annealing, and layer thickness have an effect on the grain size and on the electrical and magnetic properties of Co-Au alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The various possible parameters used for the fabrication of the Co/Cu, Co/Au and Co/Ag multilayers are listed in Table 1. Pulsed-current deposition method have been used by us and several others to deposit multilayered structures of nano-dimension of Co-Cu, Co-Au and Co-Ag and the typical deposition conditions used are respectively outlined in [60,97,105,107,[112][113][114][115] and [64,67,103].…”
Section: Experimental Methodsmentioning
confidence: 99%